Die again: a Rizzoli & Isles novel (Jane Rizzoli and Maura Isles series, 11, 1, 2014)
When Boston homicide detective Jane Rizzoli and medical examiner Maura Isles are summoned to a crime scene, they find a killing worthy of the most ferocious beast--right down to the claw marks on the corpse. But only the most sinister human hands could have left renowned big-game hunter and taxidermist Leon Gott gruesomely displayed like the once-proud animals whose heads adorn his walls. Did Gott unwittingly awaken a predator more dangerous than any he's ever hunted?